Osteogenic differentiation of human dental pulp stromal cells on 45S5 bioglass® based scaffolds in vitro and in vivo - El-Gendy, Reem; Yang, Xuebin B.; Newby, Phillipa J.; Boccaccini, Aldo R.; Kirkham, Jennifer (Tissue Engineering - Part A, 2013)
The increasing clinical demand for bone substitutes has driven significant progress in cell-based therapies for bone tissue engineering. The underpinning goals for success are to identify the most appropriate cell source and to provide three-dimensional (3D) scaffolds that support cell growth and enhance osteogenic potential. In this study, human dental pulp stromal cells (HDPSCs) were cultured under basal or osteogenic conditions either in monolayers or on 3D Bioglass scaffolds in vitro for 2 or 4 weeks. Cell-scaffold constructs were also implanted intraperitoneally in nude mice for 8 weeks. Osteogenic potential was assessed using quantitative real-time polymerase chain reaction and histological/immunohistochemical assays. In monolayer culture, osteoinductive conditions enhanced HDPSC expression of osteogenic gene markers (COL1A1, RUNX2, OC, and/or OCN) compared with basal conditions while culture of HDPSCs on 3D scaffolds promoted osteogenic gene expression compared with monolayer culture under both basal and osteogenic conditions. These results were confirmed using histological and immunohistochemical analyses. In vivo implantation of the HDPSC 3D Bioglass constructs showed evidence of sporadic woven bone-like spicules and calcified tissue. In conclusion, this study has demonstrated the potential of using a combination of HDPSCs with 3D 45S5 Bioglass scaffolds to promote bone-like tissue formation in vitro and in vivo, offering a promising approach for clinical bone repair and regeneration. © Copyright 2013, Mary Ann Liebert, Inc. 2013.